Respuesta :
The formula for difference quotient is [tex] \frac{f(x)-f(a)}{x-a} [/tex]
Here f(x) = [tex] \frac{1}{x} [/tex]
So f(a) = [tex] \frac{1}{a} [/tex]
First we shall find f(x) - f(a)
We get
f(x) - f(a)
=[tex] =\frac{1}{x}-\frac{1}{a} [/tex]
Making denominators same we get
[tex] \frac{a}{ax}-\frac{x}{ax} [/tex]
So we get
f(x) - f(a) = [tex] \frac{a-x}{ax} [/tex]
So the difference quotient shall be
[tex] \frac{f(x)-f(a)}{(x-a)}=\frac{\frac{a-x}{ax}}{(x-a)} =\frac{a-x}{ax(x-a)} [/tex]
Hence the difference quotient is
[tex] \frac{f(x)-f(a)}{(x-a)}=\frac{a-x}{ax(x-a)} [/tex]